2016
DOI: 10.1902/jop.2016.150618
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Periodontal Clinical Status on Salivary Levels of Glutathione Reductase

Abstract: Increased GR salivary concentration may be a strong/independent prognostic indicator of the amount and extent of oxidative stress-induced periodontal damage in both CP and AgP. Likewise, saliva samples might reflect an interactive effect of GR levels associated with the aging-related cumulative characteristics of periodontal damage in CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…In various studies 9 , 12 , 15 , 19 , 22 , 27 , 28 on total salivary antioxidant levels in patients with periodontitis, the antioxidant levels were lower compared to healthy individuals, consistent with the findings of this study. A recent survey by Villa-Correa et al 29 showed a significant correlation between salivary levels of glutathione reductase and periodontal clinical parameters, indicating the importance of oxidative stress processes in periodontal diseases.…”
Section: Discussionmentioning
confidence: 97%
“…In various studies 9 , 12 , 15 , 19 , 22 , 27 , 28 on total salivary antioxidant levels in patients with periodontitis, the antioxidant levels were lower compared to healthy individuals, consistent with the findings of this study. A recent survey by Villa-Correa et al 29 showed a significant correlation between salivary levels of glutathione reductase and periodontal clinical parameters, indicating the importance of oxidative stress processes in periodontal diseases.…”
Section: Discussionmentioning
confidence: 97%
“…They justify this decrease by explaining the possible damage to the antioxidants during the removal of ROS. In contrast, Trivedi Villa-Corea et al [ 110 ] showed an increase in GPX activity in the group of patients with aggressive and chronic periodontitis compared with the control group. Wei et al [ 107 ] and Yang et al [ 111 ] showed an increase in SOD activity in patients with periodontitis compared with the control groups.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 88%
“…12,43 However, some studies reported that the SOD, GR and GPX activity was higher in the saliva of patients with periodontitis as compared to that of controls. 44,45 Differences in the results of the aforementioned studies could be related to differences in methodologies, including sampling, laboratory testing, and groups that were included. One possible explanation is that there are other currently unestablished factors that contribute to the development of periodontitis.…”
Section: Antioxidants and Periodontitismentioning
confidence: 99%